2020
DOI: 10.1002/adom.202000160
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and Broadband All‐Optically Controlled THz Modulator Based on MoTe2/Si van der Waals Heterostructure

Abstract: Despite the impressive progresses in terahertz (THz) sources and detection, there is still a big challenge for high performance active optoelectronic THz devices such as THz modulators. All‐optically controlled THz modulators with large modulation depth (MD) and wide modulation bandwidth are of great importance for the THz technology. Herein, a MoTe2/Si van der Waals (vdWs) heterostructure is rationally designed as all‐optical THz modulator by taking advantage of their similar band alignment and easy integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…[25,134,136,191,203] Integrated optical modulators have also been demonstrated, including electro-optic, [23,213,243] thermooptic, [232,283] and all-optical modulators. [22,284] By virtue of their low dispersion and large anisotropic light absorption, broadband polarization-selective devices based on graphene, [26] GO, [27] MoS 2 , [215] BP, [245] and MXenes [269] have been realized. 2D materials with superior NLO properties have been used for implementing high-performance all-optical signal processing devices based on four wave mixing (FWM), [193,205] self-phase modulation (SPM), [29,216] and second-harmonic generation.…”
Section: Applications Of Integrated Devices Incorporating 2d Materialsmentioning
confidence: 99%
“…[25,134,136,191,203] Integrated optical modulators have also been demonstrated, including electro-optic, [23,213,243] thermooptic, [232,283] and all-optical modulators. [22,284] By virtue of their low dispersion and large anisotropic light absorption, broadband polarization-selective devices based on graphene, [26] GO, [27] MoS 2 , [215] BP, [245] and MXenes [269] have been realized. 2D materials with superior NLO properties have been used for implementing high-performance all-optical signal processing devices based on four wave mixing (FWM), [193,205] self-phase modulation (SPM), [29,216] and second-harmonic generation.…”
Section: Applications Of Integrated Devices Incorporating 2d Materialsmentioning
confidence: 99%
“…( B ) Transmittance of the CNT film, the f-VO 2 /CNT film, and the f-VO 2 /CNT film under electrical stimulation with a power density of 7.5 mW/mm 2 in the frequency range from 0.2 to 2 THz. ( C ) Comparison of the insertion loss and the modulation depth of the f-VO 2 /CNT THz modulator with other current-triggered or light-triggered THz modulators on substrates ( 26 , 42 51 ). ( D ) Transient response of the suspended f-VO 2 /CNT film under a square wave–modulated voltage with a frequency of 1 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…83 Another major strategy for enhancing the modulation performance of 2D-materials-based modulators is to increase carrier concentration by hybrid bulk semiconductors. 84 After years of effort, the modulation depth of 2D-based modulators has been greatly improved to nearly 100%. Nevertheless, the increase in the modulation depth is frequently associated with the higher insertion loss and slower speed of operation.…”
Section: Key Parameters For Evaluating Thz Modulationmentioning
confidence: 99%
“…118,119 Recently, Qiao et al presented an ultrasensitive modulator using a MoTe 2 /Si hybrid structure, as shown in Figure 4(D). 84 The performance of the modulator was evaluated by THz time- D-H) Reproduced with permission from Qiao et al 84 Copyright 2020, Wiley-VCH domain spectroscopy (Figure 4(E)). With this device, a record modulation performance with a modulation depth of 99.9% was reached at the laser power of 300 mW (Figure 4(F)).…”
Section: Heterostructurementioning
confidence: 99%